THE EFFECT OF TEACHING METHODS ON STUDENTS’ ACHIEVEMENT IN SPEAKING - Rismauli Aritonang; Meisuri (Universitas Negeri Medan, 2017)
This study aimed at finding out the effect of Teaching Methods on students’achievement in speaking. The population of this study was the 2015/2016eleventh grade students of SMK Negeri 1 Berastagi. The sample was divided intotwo groups namely experimental and control groups. The experimental group wastaught by applying Time Token Arend Method while the control group was taughtby using storytelling method. The test used to collect the data was oral test. Theacquired data were analyzed by using t-test. The calculation showed that tobserved(5.625) was higher than t-table (2.024) at the level of significance ( )0.05 with the degree of freedom (df) 38. The score of students taught by applyingTime Token Arend Method was higher than those taught by Storytelling Method.It can be concluded that Time Token Arend Method significantly affected thestudents’ speaking achievement.